Sleeve gastrectomy versus endoscopic intragastric balloon in decreasing weight and associated comorbidities in Erbil city: A comparative study - Saeed Ahmed , Baderkhan (Diyala Journal of Medicine, 2023)
Background: Surgical obesity treatment is difficult for both surgeons and patients. The three main categories of bariatric surgery procedures are malabsorptive, restrictive, or both in combination. Intragastric balloon (IB) is an easily applicable restrictive interventional and nonsurgical strategy for obese patients, and the surgical procedure known as laparoscopic sleeve gastrectomy (LSG) is frequently used to help obese patients decrease weight. Objective: To assess and compare these two restrictive approaches. Patients and Methods: A prospective study of 138 LSG patients was conducted, (n=82) and IB (n=56) between 1st January 2016 to 31st December 2021 in private hospitals in Erbil, Iraq. The study retrospectively evaluates patients' demographic information, changes in total body weight (TBW), changes in body mass index (BMI), and percentage of excess weight loss (%EWL), morbidities and change of comorbidities during a year of follow-up, at months 1, 3, 6, and 12 after surgery. Comparative analysis was undertaken for the follow-up results after 6 and 12 months. Results: In the IB group, 12 patients did not tolerate insertion, leaving 56; in the LSG group, 82 patients completed treatment. In terms of age (p=0.121), gender (p=0.242), and BMI (p=0.078), there were no statistical differences between the IB and LSG groups. The LSG group achieved statistically significant superior treatment outcomes in terms of changes in TBW, BMI, and %EWL. Conclusion: Both LSG and IB are beneficial in the short term for helping obese patients lose weight. IB has the benefit of being performed as an outpatient procedure with less complications, but it is less successful in helping people lose weight than LSG. The best options for various patient groups in terms of clinical outcomes and health system effectiveness must be determined through prospective, randomized control studies.